Exosome-Mediated Chemoresistance in Cancers: Mechanisms, Therapeutic Implications, and Future Directions - Gengqi Liu; Jingang Liu; Silu Li; Yumiao Zhang; Ren He (Biomolecules)
Chemotherapy resistance represents a formidable obstacle in oncological therapeutics, substantially compromising the efficacy of adjuvant chemotherapy regimens and contributing to unfavorable clinical prognoses. Emerging evidence has elucidated the pivotal involvement of exosomes in the dissemination of chemoresistance phenotypes among tumor cells and within the tumor microenvironment. This review delineates two distinct intra-tumoral resistance mechanisms orchestrated by exosomes: (1) the exosome-mediated sequestration of chemotherapeutic agents coupled with enhanced drug efflux in neoplastic cells, and (2) the horizontal transfer of chemoresistance to drug-sensitive cells through the delivery of bioactive molecular cargo, thereby facilitating the propagation of resistance phenotypes across the tumor population. Furthermore, the review covers current in vivo experimental data focusing on targeted interventions against specific genetic elements and exosomal secretion pathways, demonstrating their potential in mitigating chemotherapy resistance. Additionally, the therapeutic potential of inhibiting exosome-mediated transporter transfer strategy is particularly examined as a promising strategy to overcome tumor resistance mechanisms.